Enhanced functional stability of plasminogen activator inhibitor-1 in patients with livedoid vasculopathy - SEÇKİN GENÇOSMANOĞLU, DİLEK; EREN, FATİH (SPRINGER, 2011)
Livedoid vasculopathy (LV) is a chronic, recurrent, painful cutaneous disease with distinctive clinical features and an uncertain etiology. The skin lesions are recognizable by focal purpura, depigmentation and shallow ulcers. Thrombophilic conditions occur frequently in patients with LV. While no definitive treatment exists for LV, smoking cessation, antiplatelet therapy, immunosuppressive treatment, and anabolic steroids are often included in the therapeutic ladder. Recently, a possible link between LV and impaired fibrinolysis was established as cutaneous LV lesions responded to tissue plasminogen activator (t-PA) infusion suggesting that inhibition of the fibrinolysis through plasminogen activator inhibitor-1 (PAI-1) activity may determine the disease course in patients with LV. In this study, we investigated PAI-1 antigen (Ag) and activity levels in 20 patients with biopsy proven LV (mean age 26 +/- 11, M/F = 7/13, median disease duration 3.5 years). All patients received antiplatelet treatment with aspirin and/or dipyrimadole and 14 patients received anabolic steroids or immunosuppressive treatment. Fasting PAI-1 Ag and activity levels were measured at 9 AM in all patients. Both Ag (34 (26) ng/ml) (median (interquartile range)) and specific activity (17 (23) IU/fmole) levels of PAI-1 were moderately elevated in LV patients compared to the controls, however, PAI-1 kinetic studies demonstrated markedly enhanced stability of PAI-1 activity in plasma from patients with LV. Specific activity at 16 h was significantly higher than expected specific activity levels (7 (11) vs. 0.07 (0.09) IU/fmole, P < 0.01). While the exact mechanism of increased stability of PAI-1 activity is not known, it may be due to post-translational modifications or increased binding affinity for a stabilizing cofactor. In conclusion, enhanced stability of PAI-1 may contribute to the pathophysiology of LV, and systemic or local treatment with PAI-1 inhibitors may offer a potential treatment alternative in patients with LV.
Keywords: Livedoid vasculopathy; PAI-1 stability; Fibrinolysis; VASCULITIS; DISEASE; PAI-1; DEFICIENCY; MUTATION; LEIDEN